EVALUATION OF THE SUCCESS OF IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS AT RSUP Dr. SITANALA WITH USER SATISFACTION AS AN INTERVENING VARIABLE - Susilowati, Wahyu; Jusat, Idrus (TOPLAMA, 2025)
This study aims to assess the success of EMR implementation based on user satisfaction and net benefits, as well as to determine the supporting and inhibiting factors in EMR implementation. This study uses a quantitative method with cross cross-sectional design. The research sample used purposive sampling with a total of 84 respondents (nurses who have worked for at least 3 years).  The independent variables in this study are system quality, information quality, service quality, and user perception. The dependent variable is the net benefits, and the intervening variable is user satisfaction. Data analysis using SEM PLS. The results show that user satisfaction does not mediate the influence between system quality variables, information quality, service quality, and user perception of net benefits. System quality and information quality affect user satisfaction and net benefits. Service quality affects user satisfaction but does not affect net benefits.  User perception does not affect user satisfaction and net benefits. User satisfaction affects net benefits. The most influential independent variable is information quality.